THE (SECOND) 2024 TURNAROUND. EVEN THE COUNCIL OF EUROPE DECIDES TO REGULATE ARTIFICIAL INTELLIGENCE (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper offers a critical investigation of the Council of Europe Convention on Artificial intelligence, human rights, democracy and the rule of law. It, also, aims at disclosing the novelties, similarities and differences compared to the almost contemporary Regulation of the European Union (AI Act).
Keywords: Intelligenza artificiale; Consiglio d’Europa; Regolamentazione, tentativo di; Diritti umani; Convenzione